Human papillomavirus infection can alter the level of tumour stemness and T cell infiltration in patients with head and neck squamous cell carcinoma - Meng, Lingzhang; Lu, Heming; Li, Yueyong; Zhao, Jingjie; He, Siyuan; Wang, Zechen; Shen, Jiajia; Huang, Huixian; Xiao, Jinru; Sooranna, Suren Rao; Song, Jian (Frontiers in Immunology, 2022)
Head and neck squamous cell carcinoma (HNSCC) usually has a poor prognosis and is associated with a high mortality rate. Its etiology is mainly the result from long-term exposure to either alcohol, tobacco or human papillomavirus (HPV) infection or a combination of these insults. However, HNSCC patients with HPV have been found to show a survival advantage over those without the virus, but the mechanism that confers this advantage is unclear. Due to the large number of HPV-independent HNSCC cases, there is a possibility that the difference in prognosis between HPV-positive (HPV+) and negative (HPV-) patients is due to different carcinogens. To clarify this, we used scRNA data and viral tracking methods in order to identify HPV+ and HPV- cells in the tumour tissues of patients infected with HPV. By comparing HPV+ and HPV- malignant cells, we found a higher level of tumour stemness in HPV- tumour cells. Using tumour stemness-related genes, we established a six-gene prognostic signature that was used to divide the patients into low- and high-risk groups. It was found that HPV patients who were at low-risk of contracting HNSCC had a higher number of CD8+ T-cells as well as a higher expression of immune checkpoint molecules. Correspondingly, we found that HPV+ tumour cells expressed higher levels of CCL4, and these were highly correlated with CD8+ T cells infiltration and immune checkpoint molecules. These data suggest that the stemness features of tumour cells are not only associated with the prognostic risk, but that it could also affect the immune cell interactions and associated signalling pathways.